Circulatory collapse requiring mechanical circulatory support in a child with autoimmune adrenal insufficiency: a case report - Hejazi, Yahia; Tegtmeyer, Ken; Chlebowski, Meghan; Gist, Katja M. (BMC pediatrics, 2024)
Background We report a rare case of new onset autoimmune adrenal insufficiency in childhood, presenting with severe shock requiring mechanical circulatory support. In the current era of readily available imaging, laboratory and other diagnostic investigations, medical history and careful physical exam can often provide valuable diagnostic information for timely therapy. Case presentation A 7-year-old boy with a history of mild intermittent asthma, presented with severe cardiogenic shock requiring extracorporeal membrane oxygenation (ECMO). Bronzing of his entire body was noted on physical exam. Stress dose hydrocortisone was given for suspected adrenal insufficiency. After weaning from ECMO and extensive rehabilitation, the patient recovered and was discharged home. Conclusion Primary adrenal insufficiency (PAI) should be considered in the context of physical exam and laboratory findings, even in the presence of circulatory shock.